Dampak Ekspansi Biomassa sebagai Energi Terbarukan: Kasus Energi Terbarukan Indonesia - Syaifuddin Yana; Nelly Nelly; Radhiana Radhiana; Nasir Ibrahim; Awal Afrizal Zubir; T.M. Zulfikar; Ardhana Yulisma (Fakultas Teknik, 2022)
Energy is vital to Indonesia's economy, acting as a source of consumption and production across many industries. Sustainable development approaches should be employed to maximise energy use for the common good. A literature study on biomass as renewable energy (RE) in ASEAN and Indonesia. ASEAN countries want to reach 23% renewable energy by 2025, according to the meeting's outcome. The ASEAN Government slashed fuel subsidies and fossil fuels and increased regional market integration and project execution speed to attain the 23% renewable energy objective by 2025. Indonesia’s renewable energy sources are many. Indonesia’s renewable energy development is not as advanced as other countries’. In 2017, the country added 9 GW of renewable energy capacity. Indonesia produce 146.7 million tonnes of biomass in 2019, or 470 GJ/year. Indonesia has a lot of biomass energy potential, so it should keep producing/using renewable energy as much as feasible for society, and its management should follow sustainable development principles.